Conceptual design of a winged hybrid airship - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Ali, JS Mohamed (2014)
The present study focuses on the sizing and aerodynamic contour design of a two-seater 1000 kg gross take-off mass winged hybrid airship. Unlike the conventional hybrid airships, which stay aloft and takeoff with the help of VTOL propulsion systems, a winged hybrid airship requires a certain speed to takeoff by utilizing lift coming from its aerodynamic surfaces. Heaviness fraction and takeoff ground roll are considered as measure of merit in initial sizing. Based on the design requirement of Malaysian inter-island tourism and transportation of agricultural products, range is set to 450 km and ground roll for take-off about 150 m. For the airship to be heavy enough for ground handling, the ratio of hydrostatic to hydrodynamic lift is set equal to 49:51. Summary of the results to be obtained in early design phase will give a baseline start to study the aerodynamics and stability characteristics of such airships in future.